Legal Status of Asylum Seekers and Refugees in Iraq and Kurdistan Region of Iraq - Adnan Amin Qadir (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
Iraq and Kurdistan Region of Iraq host more than 295,000 refugees and asylum seekers and yet do not have an inclusive national law to grant refugee status thorough fair and efficient refugee status determination (RSD) procedure. In the absence of such legal procedure, the majority of refugees in Iraq and KR-I enjoy a temporary status called “asylum seeker” status. The Political Refugee Law no. 51 of 1971 however, recognizes political and military refugees excluding categories of persons seeking asylum in Iraq for reasons of race, religion, ethnicity, membership of a particular social group and finally persons fleeing conflicts and wars. The fact that Iraq is not a party to the 1951 Convention Relating to the Status of Refugees and its 1967 Protocol makes protection of non-political refugees more problematic mainly because their status is tied in short and long terms to protection matters such as admission, Non-Refoulement, detention and access to rights and durable solutions. In practice, the United Nations High Commissioner for Refugees (UNHCR) and KR-I authorities grant asylum seeker status to those who do not fall under the 1971 Law in Iraq. It is witnessed however, that these non-political asylum seekers are at risk of denial to admission, detention and Refoulement because of the lack of an inclusive refugee law to recognize them and the existence of residency related laws that penalize illegal border crossing and illegal presence in Iraq. Moreover, Iraqi asylum system do not establish a comprehensive approach with regard to durable solutions representing in local integration, voluntary repatriation and resettlement because firstly it does not grant refugee status to all refugees which is considered the first brick in securing refugee rights and self-reliance toward durable solutions, and secondly, Iraq has taken measures to restrict essential rights of refugees including right to movement, right to work and right to naturalization. This research analyzes granting and denying asylum seeker and refugee statuses to persons seeking asylum in Iraq and Kurdistan Region in the light of applicable laws and regulations and its un-unified implementation and then examines the protections risks associated to these issues aiming at reaching some solutions.